Huslæreren på Egelykke - Albeck, Gustav (Grundtvig-Studier, 1959)
The Tutor at Egeløkke. By Gustav Albeck. By introducing some new source material (Grundtvig’s “Character and Lesson Book for Karl Steensen de Leth”, written in the period from March to November, 1806), this essay seeks to shed new light on the frequently discussed subject: Grundtvig’s stay at the manor of Egeløkke on Langeland and his violent infatuation for the lady of the house, Fru Constance Leth, née Fabritius de Tengnagel. The Character Book is written in a sober and practical tone throughout, and gives an account from week to week of Grundtvig’s work as tutor for Constance’s son, Karl. It is introduced by a series of pedagogical reflections, in which Grundtvig does not try to hide his scanty knowledge and experience as a teacher, but which nevertheless surprise us by their deep insight and a freedom from prejudice which tempt us to characterise them as completely mature. The Character Book shows that Grundtvig made great demands on the memory and power of understanding of his pupil, who was only eight years old, especially in Geography and in Grundtvig’s favourite subject, History. In the last-named subject Grundtvig frequently succeeded in arousing his young pupil’s warm interest and enthusiasm, and the History lessons were not seldom the bright spots in Grundtvig’s days at Egeløkke, which were often full of anguish. These feelings of anguish were a consequence of his having fallen in love with the lady of the house. In the spring months of 1805, when he had newly arrived at Egeløkke, he experienced for a short time an intense, intoxicating happiness. Probably, unacquainted as he was with the free and easy manners which were characteristic of social life in the Danish manor-houses at the time of the Napoleonic War, he may have read a good deal more into the kindness and sympathy which Fru Constance showed him than he was justified in doing. The pages of his diary, of which only fragments have been preserved, show that he suffered great moral distress for a while, because his love was for a married woman, but he realised quite early, presumably by the end of the summer of 1805, that his feelings for the lady were not returned – or rather, perhaps, discovered to his surprise that he was not the only one to receive kindness, signs of affection and gentle glances from the fair one. From time to time the pages of the diary bear witness to his jealousy and a growing offence because of the adored one’s behaviour, an offence which developed into very harsh accusations and which, probably around July 15th, 1806, caused a violent dispute with the lady, during which, angry and indignant, she repudiated his harsh accusations and offensive suspicions. The Character Book is of value as a supplementary source together with the scattered and only partially preserved diary entries, since it shows that Fru Constance annoyed Grundtvig almost every day by disturbing and interfering with his work as a teacher, partly by arbitrarily giving Karl an exceptional amount of freedom from his lessons, and partly by the extensive sociability and entertaining which upset the regular daily routine at Egeløkke and, to no less an extent, impaired the jealous tutor’s peace of mind. From the last couple of years at Egeløkke no diaries or source material of that kind from Grundtvig’s hand have been preserved. To that period belong his first printed works, especially concerning Scandinavian mythology - evidence that he was in process of freeing himself from the slavery in which his youthful infatuation for the fair mistress of the house had bound him, as he has also poetically described it in his famous poem: “Strandbakken ved Egeløkke” (“The Hill by the Strand at Egeløkke” ). Only during his great religious (and ethicsl) crisis in 18 10 - 1 1 did he completely free himself from his longing for Constance. In a draft for his last poem to her (written for her birthday on April nth, 1 8 1 1 ) he described his earlier poems to her as the outcome of “The envious pain of wounded pride And feelings that were never in my heart”. The words did not appear in the completed poem, and, even if they seem a trifle too honest and self-critical, still, as a perusal of the extant source material shows, they come amazingly near the truth about his relations with Constance, as they took shape after the intoxicating transport of happiness had worn off.